Fluorescent Nanomaterials for Color‐Multiplexing Test Papers toward Qualitative/Quantitative Assays. Issue 7 (30th April 2018) - Jiang, Changlong; Liu, Bianhua; Han, Ming‐Yong; Zhang, Zhongping
Abstract: Paper‐based sensors (e.g., pH and pregnancy test papers) are the most promising sensors because analysts prefer on‐site and real‐time/visual detection without the aid of analytical instruments. Herein, advances in the new generation of nanofluorophore‐integrated test papers toward visual qualitative/quantitative assays of universal target species are described. The main aspects of the advances gained from a decade of work are summarized here: i) novel strategies for colorimetric assays on test papers are described by exploiting the paramount advantages of fluorescent nanomaterials, such as wide excitation wavelength, narrow/tunable emission, and surface‐modification flexibility; ii) motivated and driven by the challenges to upgrade the classical test papers, an established library of fluorescent nanoprobes with supersensitive visualizing capability through the molecular engineering of nanomaterial surfaces and the rational design of spectral responses is described, which is aimed at implementing the on‐site and real‐time/visual detection of universal analytes such as explosives, pesticides, food additives, metal ions, and biological molecules; iii) molecularly engineered fluorescent nanoprobes are then formulated into inks for inkjet‐printing test papers, greatly overcoming the technical challenges of test papers in reliability and reproducibility. Finally, a conceptually innovative framework of nanofluorophore‐integrated test papers that enable color‐multiplexing quantitative assays of universal analytes is established. Abstract : Test sensors with integrated fluorescent nanomaterials are the most promising sensors because analysts prefer visual detection without the aid of analytical instruments. Recent progress in the new generation of nanomaterials‐integrated test papers towards visual assays of universal target species is reviewed. This provides more in‐depth understanding of the structure–property relationships of color‐multiplexing test papers and the design of new fluorescent materials.